Analysis of Determinants of the Effectiveness of Competency Certification in Improving Administrative Performance at Provincial General Hospitals in Central Java - Ahmad, Baharuddin; M, Rosliana (INDOGENIUS, 2025)
Background & Objective: Improving the quality of hospital services depends not only on medical personnel, but also on the role of professional and competent administrative staff. Competency certification is one strategy for improving the quality of non-medical human resources, but its effectiveness remains questionable in many public service institutions. This study aims to analyze the influence of perceived benefits of certification, organizational support, and individual competence on the administrative performance of non-medical staff at regional public hospitals (RSUD) in Central Java Province. Method: This study uses a quantitative approach with an explanatory survey design. Data were collected from 45 respondents through a closed-ended questionnaire and analyzed using multiple linear regression. Validity, reliability, and classical assumptions tests were conducted to ensure data quality. Result: The results indicate that all three independent variables simultaneously and partially significantly influence administrative performance (Adjusted R² = 0.574, p < 0.05). Individual competence is the most dominant factor (β = 0.341), followed by perceived benefits of certification (β = 0.312) and organizational support (β = 0.278). Conclusion: The effectiveness of competency certification is not solely determined by the presence of a certificate but is significantly influenced by individual readiness and workplace support. Certification programs in hospitals should be designed with consideration for the integration of human resource development policies, incentive systems, and competency-based performance evaluation.